مؤشرات الكفاءة المهنية في الممارسة الإعلامية بالجزائر محاولة بناء مقياس - هديل عبداللاوي; تيسير نوبة (جامعة الوادي - University of Eloued, 2025)
"هدفت هذه الدراسة إلى الكشف عن واقع الكفاءة المهنية لدى الصحفيين العاملين في المؤسسات الإعلامية محل الدراسة بولاية الوادي، بالإضافة إلى بناء مقياس علمي يتيح تقييم هذه الكفاءة استنادا إلى خمسة مؤشرات أساسية، هي: التحرير، التقديم والتنشيط أخلاقيات المهنة ومواثيق الإعلامية ، المستوى الثقافي، والمستوى التقني. وقد اعتمدت الدراسة على المنهج المسحي الذي يستهدف تسجيل وتحليل وتفسير الظاهرة، وذلك باستخدام أداة مقياس ليكرت الخماسي الموجه إلى الصحفيين في ثلاث مؤسسات إعلامية محلية، وهي: إذاعة الجديد، إذاعة التحرير، وإذاعة الوادي. تم تطبيق المسح الشامل على مجتمع الدراسة كاملاً والمكون من (40) صحفيا. وقد توصلت الدراسة إلى النتائج التالية: تفاوت في مدى امتلاك الصحفيين المؤشرات الكفاءة المهنية المعتمدة في المقياس. ضعف في إتقان أساسيات التحرير لدى بعض الصحفيين، ما يدل على محدودية الوعي التحريري المطلوب. مستوى مقبول في مهارات التقديم والتنشيط، دون أن يصل إلى حد الكفاءة المهنية المطلوبة. قصور في الإلمام بأخلاقيات المهنة، مما يضعف الالتزام بالمعايير المهنية المعتمدة. إلمام تقني متوسط لا يواكب متطلبات الممارسة الإعلامية الحديثة. مستوى جيد من الوعي الثقافي لدى الصحفيين، رغم بعض أوجه القصور. يمثل المقياس المقترح أداة مرجعية يمكن الاعتماد عليها مستقبلاً في تقييم الأداء الإعلامي وفق معايير موضوعية" "This study aimed to uncover the reality of professional competence among journalists working in the media institutions under study in the Wilaya of El Oued. Additionally, it sought to construct a scientific scale to evaluate this competence based on five key indicators: editing, hosting and presentation, professional ethics and media codes, cultural level, and technical level. The study employed the survey method, which aims to record, analyze, and interpret the phenomenon using a five-point Likert scale directed at journalists in three local media institutions: Radio El Jadid, Radio El Tahrir, and Radio El Oued. A comprehensive survey was conducted on the entire study population, consisting of 40 journalists. The study reached the following results: A variation in the journalists possession of the professional competence indicators included in the scale. A weakness in mastering the basics of editing among some journalists, indicating limited editorial awareness. An acceptable level in hosting and presentation skills, yet not reaching the required level of professional competence. A lack of familiarity with professional ethics, weakening adherence to established professional standards. A moderate level of technical proficiency that does not keep pace with the demands of modern media practice. A good level of cultural awareness among journalists, despite some shortcomings. The proposed scale represents a reference tool that can be relied upon in the future to evaluate media performance according to objective standards."
مذكرة ماسترقسم اعلام واتصال تخصص سمعي بصري
Keywords: إذاعة الوادي; إذاعة التحرير; إذاعة الجديد; الصحفيين; الممارسة الإعلامية; الكفاءة المهنية; مؤشرات; Indicators; Professional Competence; Media Practice; Journalists; Radio El Jadid; Radio El Tahrir; Radio El Oued: